Planificación del sistema de gestión de la calidad en Biomedics I.P.S EU, bajo la norma NTC 9001:2015 (2019)
The application of quality management systems has become a great competitive advantage within various sectors, since an organization provides the improvement and enhancement of its processes focused on customer satisfaction, which in turn provides a mayor generation of operating income. The following project corresponds to the planning of the quality management system, following the requirements of the NTC ISO 9001: 2015 standard, for BIOMEDICS IPS EU, based in the city of Duitama, consolidated as an institution providing medical services with principles and scientific bases in homotoxicology, with nearly 27 years of experience and headed by Dr. Jaime Octavio Neira Pinzón. For the development of this project, secondary information corresponding to the corresponding physical and digital documentation was taken into account by the company, on the other hand, the primary information was collected using two methods, quantitative by user satisfaction surveys, and qualitative through an in-depth interview with the process leader. The detailed recognition of the organization was carried out and the strategic platform for it was structured, in addition to this, an analysis of the gap was made evaluating its current situation and the projection of the application of an improvement plan in the principles or requirements where shortcomings are contemplated. It is concluded that the application of a quality management system for BIOMEDICS I.P.S is a useful mechanism to mitigate the shortcomings that were identified in the course of this investigation, which is why its execution within it is recommended.